-10+14g=14g

Simple and best practice solution for -10+14g=14g equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -10+14g=14g equation:


Simplifying
-10 + 14g = 14g

Add '-14g' to each side of the equation.
-10 + 14g + -14g = 14g + -14g

Combine like terms: 14g + -14g = 0
-10 + 0 = 14g + -14g
-10 = 14g + -14g

Combine like terms: 14g + -14g = 0
-10 = 0

Solving
-10 = 0

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| (8x-3)-(4x+1)= | | (2x+3)(-4x+7)=0 | | 0=2a^2-5a-1 | | x^2-7x+3=20 | | F(y)=-3y-2 | | 0.12-0.28=0.8 | | 100(0.17x+0.7(x-2))=100(0.01(4x-1)) | | -19x+3y=-5 | | xy+4=10 | | -14+5-c-3=x+6+x+3x | | 6(3x-4)=14 | | x+1.6x=92 | | 5m+15m=80 | | x+1.6x=93 | | -4(Z+5)=16 | | 9x-6=6x+9 | | 4.5q-4.6-4.6q=-1.1q-1.3 | | 7x=9x-6 | | y=90x+150 | | 5.2q-2.5-5.1q=-0.9q-3.5 | | 6(x-7)+4=6x+7 | | -3b+3b= | | -9+5x=31 | | 3(X+5)+4(2X-8)=5(2X+1) | | 6x+4+4x+9=9x+3 | | 0.8x-12=1.3x-17 | | 0.17x+0.7(x-2)=0.01(4x-1) | | x+5/2=15-x/3 | | 4p+3=5+3p | | X(3X-14)=-9 | | -2(4y-3)-y=-2[y-3) | | 6.2x-3=5.2 |

Equations solver categories